COVID-19 epidemic in Libya. Issue 1 (1st January 2021) - Bredan, Amin; Bakoush, Omran
ABSTRACT: The first case of COVID-19 was identified in Libya on 24/3/2020, and about 2 months later, the number of reported COVID-19 cases started to increase notably. The outbreak was first prominent in the southern region (Sabha) and then spread to the western and eastern parts of Libya. By 24/12/2020, the reported total number of deaths from COVID-19 reached 1415. There seems to be no published data on the size of the epidemic in Libya. Here, we estimated the number of Libyans exposed to COVID-19 by using a COVID-19 mortality adjusted mathematical model for the spread of infectious diseases. We estimated that 14–20% of the Libyan population have been exposed to the COVID-19 pandemic. Thus, the risk of spread of COVID-19 infections during the coming months is high, and a considerable number of Libyans, particularly the elderly and people with chronic diseases, should be protected against COVID-19 infection. This is particularly urgent in the light of unofficial reports that the relevant healthcare facilities are under extreme stress.